KINERJA PELAYANAN POS BANTUAN HUKUM DI PENGADILAN KELAS-IA PONTIANAK - Prihantono, Prihantono (Khatulistiwa, 2013)
The presence of the POSBAKUM (legal Aid Post) of course needs serious attention and in-depth study in order to provide efficiency and effectiveness assessment especially related to the service of the POSBAKUM. Therefore, this research was conducted to help gather information related to the POSBAKUM service performance. To make it more focused, fundamental questions are important. Thus, in this study, the questions used are as follows: How is the performance of the Legal Assistance at the Religious Court class 1-A Pontianak?; how is the restructurization of the POSBAKUM services done?; and what are the opportunities and challenges of the POSBAKUM at the Religious Court class 1-A Pontianak. Through these questions, this research aims to describe the performance of service provided by the POSBAKUM at the Religious Court class I-A Pontianak. The study also attempts to present the efforts of restructurization of the POSBAKUM at the Religious Courts in class I-A Pontianak. More importantly this study is to find out the opportunities and challenges of the service provided by the POSBAKUM at the Religious Courts in class I-A Pontianak. With this research, the POSBAKUM will be "evaluated" to maximize the success rate and giverecommendations to fix flaws in providing the best service to the public in the future.